2018
DOI: 10.4103/sjmms.sjmms_175_16
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus colonization among Saudi women during labor

Abstract: Background:The presence of group B streptococcus in the genital area during pregnancy and labor is associated with high neonatal morbidity and mortality. However, the exact prevalence of group B streptococcus among Saudi women has not yet been established.Objective:The aim of this study was to determine the prevalence of group B streptococcal colonization in Saudi pregnant women as a primary end-point and neonatal complications as a secondary end-point.Materials and Methods:A prospective, observational, cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In Nigeria, prevalence values ranging from 4% -18% have been reported [1][2][3][4]. Reports from some other countries have revealed prevalence rates such as 20.9% in Ethiopia [5], 19% in Saudi Arabia [6] and14% in Brazil [7]. GBS colonization of the birth canal during pregnancy has been noted to result in miscarriage, stillbirths, prematurity and neonatal sepsis [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, prevalence values ranging from 4% -18% have been reported [1][2][3][4]. Reports from some other countries have revealed prevalence rates such as 20.9% in Ethiopia [5], 19% in Saudi Arabia [6] and14% in Brazil [7]. GBS colonization of the birth canal during pregnancy has been noted to result in miscarriage, stillbirths, prematurity and neonatal sepsis [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…[ 18 19 ] Recent studies from Middle Eastern countries also show significant variance in the prevalence of GBS colonization. [ 13 14 15 18 19 20 24 ] The varying rates of colonization can be partly explained by difference in socioeconomic groups, education level and acceptance of medical and diagnostic facilities.…”
Section: Discussionmentioning
confidence: 99%
“…From the Middle East, studies have found the prevalence of maternal GBS colonization to range from 3.3% to 31.6%;[ 13 14 15 ] however, there is no recent study from the United Arab Emirates (UAE) reporting the clinico-bacterial profile, prevalence, and antibiotic sensitivity pattern. Accordingly, this study was conducted to determine the prevalence of GBS colonization in pregnant women from UAE after 35 weeks of gestation as well as determine their clinical profile, the maternal and fetal outcome of those colonized with GBS, and the antibiotic sensitivity pattern of GBS.…”
Section: Introductionmentioning
confidence: 99%
“…Group B Streptococcus (GBS), also known as Streptococcus agalactiae, is an encapsulated gram-positive diplococcus, normally found in the female urogenital tract and rectum. Vaginal colonization of GBS can lead to maternal and neonatal complications, even when it is asymptomatic [ 1 ]. Vertical transmission of GBS before or during delivery is a major cause of premature rupture of the membranes, pre-term delivery, and low birth weight.…”
Section: Introductionmentioning
confidence: 99%
“…Early and late onsets are two different forms of the disease. The most common cause of neonatal GBS disease is an early-onset infection, which usually occurs within the first week of life, whereas late-onset infection occurs anytime up to three months postpartum [ 1 ]. The prevalence of maternal GBS colonization varies from 15% to 30% worldwide [ 3 ]; however, in Saudi Arabia, different regions have reported a range of 9.2%-31.6% [ 2 ].…”
Section: Introductionmentioning
confidence: 99%